“Estudio técnico económico para la instalación de una planta procesadora de chancaca granulada, en la Región San martín - Rubio Gómez, Oscar Augusto (2005)
This study project aims to assess the most appropriate and / or favorable for the installation of a processing plant chancaca, in the region of San Martín economic, financial and social, political, environmental and legal indicators; for which absolved each of the specific goals outlined in the project, seeking to give them accurate answers, based on the results of economic research and finance. The plant will use the existing sugar cane in major production areas, the same as for its commercial nature cough sugarcane growers remain limited income from the sale of their products, giving the reduced economic activity expectations. The project has raised the challenge through proper planning from the technical point of view, increasing per capita consumption of granulated brown sugar, promoting the consumption of the product in order to achieve substitution in consumption habits brown sugar for a product good quality, in a not too distant future; ie the project seeks overcrowding in consumption in the region San Martin. The project has established mechanisms for promotion through the implementation of a marketing mix that allows reaching customers and achieve the positioning of the product, for which it will make use of nutritional benefits, dietary, medicinal and natural process in obtaining in addition to the organoleptic quality and adequate sanitation in the product, which will venture into potential product markets. The project seeks at all times to serve as a reference standard for the installation of new companies and industries dedicated to the processing of agricultural products in general, livestock, forestry among others in the region San Martin. And thus achieve the development of regional agribusiness.